Transcriptome analysis and gene expression analysis related to salinity-alkalinity and low temperature adaptation of Triplophysa yarkandensis - Zhang, Xuejing; Wang, Tai; Zhai, Dongdong; Liu, Hongyan; Xiong, Fei; Wang, Ying (Frontiers in Genetics, 2023)
As a common species of Triplophysa, Triplophysa yarkandensis is distributed in Shule river of Hexi Corridor, Gansu province in China. In order to enrich gene database resources and explore the environment adaptation of T. yarkandensis, fifteen tissues were collected from three adult T. yarkandensis for transcriptome sequencing and de novo assembly. Nine major international gene annotation databases (NR, COG, egg_NOG, TrEMBL, Pfam, KOG, Swiss prot, KEGG and GO) were utilized to annotate unigenes. A profound study was conducted to explore the gene expression and the differentially expressed genes among five tissues (brain, heart, kidney, liver and spleen). In addition, it’s found in this research that candidate genes involved in salinity-alkalinity and low temperature adaptation were differentially expressed in tissues of T. yarkandensis. For instance, gpx1, abcc1 and cat genes participated in the regulation process of salinity-alkalinity adaptation, while elovl4, acaca and fasn genes were involved in fatty acid metabolism and closely associated with low temperature adaptation. Furthermore, the expression of these genes differed among different tissues. The transcriptome information in this study will be conducive to provide a brand understanding for the molecular level research and further exploration of the environmental adaptation of T. yarkandensis.